Pengaruh Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Mediator Pergerakan Ekonomi - Nailin Nikmatul Maulidiyah, Rizqy Ridho Ilahi (ACTIVA: Jurnal Ekonomi Syariah, 2019)
The purpose of this study is to determine the impact of physical work environment on job satisfaction, the impact of physical work environment on employee performance, the impact of job satisfaction on employee performance, the role of job satisfaction in mediating the impact of physical work environment on employee performance. The type of this research is a literature review which describes the effect between variables based on existing theories and empirical studies of relevant journals. The results of this study showed that physical work environtment has a positive effect on job satisfaction, physical work environtment has a positive effect employee performance, job satisfaction has a positive effect on employee performance, physical work environment has a positive effect on employee performance through job satisfaction. Keywords: Physical Work Environment ; Job Satisfaction ; Employee Performance